Thematic Community Service during Ramadan: Opportunities, Challenges, and Relevance within the Kampus Merdeka Framework - Taqiyuddin, Muhammad; Hapzi, MHD; Hidayat, M.Alif; Wahyudi, Sidiq; Akmal, Azzam Alfatih; Al-Mujaddidi, Shibghah; Naufal Rabbani, Muhammad (ASSUNNAH PRESS, 2025)
Thematic Community Service Program (KKN Tematik) has measurable performance targets and a clear thematic focus, enabling students to make tangible contributions to community life, particularly in religious and social sectors. Activities include religious education, the development of majelis ta’lim (Islamic study groups), Islamic festivals, MSME mentoring, as well as health education and digital literacy. Through a participatory approach, students can act as catalysts for change, strengthen Islamic values, and raise community awareness of local issues. However, the limited duration of the program makes social adaptation faster and more challenging, thus requiring more systematic and intensive program planning. Community service activities using the ABCD (Asset-Based Community Development) method yield several important conclusions. Despite the short duration of the KKN, activities tend to be more compact and impactful. Overall, the community and village government where the KKN is held are receptive to the activities. Communities often need assistance and guidance in managing religious activities in rural areas. Students also demonstrate significant potential to integrate easily with the community, particularly through this point of contribution